2020
DOI: 10.1136/neurintsurg-2020-015889
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor clinical outcome despite complete reperfusion in acute ischemic stroke patients

Abstract: BackgroundIn patients suffering from acute ischemic stroke from large vessel occlusion (LVO), mechanical thrombectomy (MT) often leads to successful reperfusion. Only approximately half of these patients have a favorable clinical outcome. Our aim was to determine the prognostic factors associated with poor clinical outcome following complete reperfusion.MethodsPatients treated with MT for LVO from a prospective single-center stroke registry between July 2015 and April 2019 were screened. Complete reperfusion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 37 publications
10
70
1
Order By: Relevance
“…Our study demonstrated that baseline NIHSS score, ICA occlusion, and DCM are independent predictors of poor functional outcome despite successful recanalization after MT within 6 h of symptom onset. Our finding of higher NIHSS score and its association with the poor functional outcome is consistent with several previous studies which evaluated the prognostic factors of outcome after MT ( 7 9 ). A high NIHSS on admission was also associated with both proximal ICA occlusion and poor collateral circulation ( 10 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our study demonstrated that baseline NIHSS score, ICA occlusion, and DCM are independent predictors of poor functional outcome despite successful recanalization after MT within 6 h of symptom onset. Our finding of higher NIHSS score and its association with the poor functional outcome is consistent with several previous studies which evaluated the prognostic factors of outcome after MT ( 7 9 ). A high NIHSS on admission was also associated with both proximal ICA occlusion and poor collateral circulation ( 10 ).…”
Section: Discussionsupporting
confidence: 92%
“…Given the growing and widespread utilization of endovascular clot-extraction in LVO stroke and lack of additional means to counter the deleterious mechanisms of ischemia and reperfusion injury (12,85), SEBC is an appealing concept to reap the benefits of therapeutic hypothermia while minimizing the adverse effects of systemic hypothermia. Based on our current understanding of the mechanisms of stroke, reperfusion, and therapeutic (brain) hypothermia, it is reasonable to consider an improvement in outcome and reduction in the occurrence of post-stroke ICH may occur.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported rate of good post-MT functional outcome (modified Rankin Scale [mRS] score of 0-2 at 90 days) was < 50% [1]. Reported futile recanalization causes include old age, moderate and severe stroke, surgical-and instrument-related complications, delayed opening of blood vessels, distal vascular embolisms, and reocclusion [9][10][11]. Therefore, it is important to recognize poor outcome factors and select the most suitable patients for MT to improve the proportion of good outcomes.…”
Section: Introductionmentioning
confidence: 99%